The vocational education sector in relation to labour market expectations. The analysis of the results of an international student survey - Kwiatkowska-Ciotucha, Dorota; Załuska, Urszula (Sektor kształcenia zawodowego wobec oczekiwań rynku pracy. Analiza wyników międzynarodowego badania ankietowego uczniów, 2022)
The article presents an analysis of the results of a survey conducted in 2022 among students and young graduates of three vocational education courses, studying in EU countries (N = 428). The area of research concerns the awareness of competencies sought-after by employers and the self-assessed level of these competencies. The authors used tests of the equality of two means in order to check for differences in assessments according to the respondents’ metric characteristics, and also factor analysis to check for similarities in attitudes towards different types of competencies in the respondents’ assessments. Finding such similarities would allow to use a summative scale and reduce the dimensions.
Econometrics = Ekonometria, 2022, Vol. 26, No. 3, s. 35-53
Keywords: vocational education; the importance of competence; self-assessment of the level of competence; questionnaire research; statistical analyses; szkolnictwo zawodowe; znaczenie kompetencji; samoocena poziomu kompetencji; badania kwestionariuszowe; analizy statystyczne